Climate Change in Linguistic Schoolscapes: Patterns and Language Use - Solihah, Nining Ma'rifatus; Anjaniputra, Agung Ginanjar (Interference: Journal of Language, Literature, and Linguistics, 2024)
Abstract. In educational settings, one effort to mitigate effects of climate change is through the display of Linguistic Landscapes (LLs). The signage can bring about changes and contribute to good practices to avert and reduce the impact of climate change (CC). Therefore, this study aims to find out the sign patterns and to describe the language use in the LLs related to CC. This study documented 351 signs in four senior high schools in Kebumen, Central Java, Indonesia, which were then qualitatively portrayed. To reveal the language used in LSs related to CC, the data were classified based on language patterns. The findings of the study show that the sign patterns applied in CC LSs are monolingual and bilingual patterns involving Indonesian, English, French, and Javanese with Indonesian as the dominant language, English and French as foreign languages, and Javanese as the leased used language. Meanwhile, in terms of language use related to CC Indonesian is used as communication and translation function to deliver CC messages, English and French are used as media to learn languages and to deliver international topics related to CC, and Javanese is used to maintain both its language and the environment. This study has shown that LSs to some extent contribute to the community's adaptation and mitigation to climate change by lowering the impact and cause of the crisis. Keywords: Climate Change, Linguistic Landscape, Linguistic Schoolscape, Language Use